2017
DOI: 10.1136/neurintsurg-2017-013224
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment predictors of malignant evolution in patients with ischemic stroke undergoing mechanical thrombectomy

Abstract: in our study a clinical and radiological features-based model was strongly predictive of MMI evolution in AIS. High SBP and BG on admission and, especially, a CTA ASPECTS ≤5 may help to make decisions quickly, regardless of time to treatment and successful reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 22 publications
2
23
1
Order By: Relevance
“…23 Furthermore, our study made adjustments for post-treatment powerful predictors of MMI, infarct size and PH2, which were not included in the previous analyses. 22,23 In particular, our results are in agreement with the recent secondary analyses from data of randomized controlled trials, which suggested that baseline collateral status on CTA is a robust determinant of clinical outcomes in patients undergoing ET. 18,24 Thus, the treatment benefit may be absent in patients with poor collateral circulation.…”
Section: Journal Of Neurosonology and Neuroimagingsupporting
confidence: 91%
See 1 more Smart Citation
“…23 Furthermore, our study made adjustments for post-treatment powerful predictors of MMI, infarct size and PH2, which were not included in the previous analyses. 22,23 In particular, our results are in agreement with the recent secondary analyses from data of randomized controlled trials, which suggested that baseline collateral status on CTA is a robust determinant of clinical outcomes in patients undergoing ET. 18,24 Thus, the treatment benefit may be absent in patients with poor collateral circulation.…”
Section: Journal Of Neurosonology and Neuroimagingsupporting
confidence: 91%
“…22,23 A study showed that CTA-SI ASPECTS was an independent predictor of MMI in a model that did not include collateral status. 22 In fact, CTA-SI ASPECTS may reflect abnormalities of cerebral blood volume at tissue level. Thus it may correspond to final infarct volume and clinical outcomes.…”
Section: Journal Of Neurosonology and Neuroimagingmentioning
confidence: 99%
“…The multivariate model used in our study was as follows : 1) selection of independent variables. We included those CTA variables determined to have been associated with sICH or MMCAI from previous studies 3,5,15) . We analyzed the area under the receiver operating characteristic curve (AUC-ROC) to determine the best cut-off point of the CTA parameters to identify patients with sICH and/or MMCAI after EVT in the derivation cohort.…”
Section: Statistics Analysismentioning
confidence: 99%
“…110 Clinical factors that were predictive of impending malignant infarction post-EVT were a high NIHSS (≥ 20 or ≥15 for left and right hemispheres respectively), a high admission BP, and hyperglycemia (with failure of control within 48 hours). 111,112 Radiologically, the strongest predictor was a CT ASPECTS (Alberta Stroke Program Early CT Score) ≤ 5 or a diffusion-weighted imaging (DWI) core volume of > 80 mL with a low sensitivity but high specificity. 111,113 Other measures: Patients may be extubated based on the neurologist/anesthetist's assessment.…”
Section: Posttreatment Managementmentioning
confidence: 99%
“…111,112 Radiologically, the strongest predictor was a CT ASPECTS (Alberta Stroke Program Early CT Score) ≤ 5 or a diffusion-weighted imaging (DWI) core volume of > 80 mL with a low sensitivity but high specificity. 111,113 Other measures: Patients may be extubated based on the neurologist/anesthetist's assessment. Airway support and ventilator assistance may be continued if there is evidence of continued depressed sensorium or lack of airway protection secondary to bulbar dysfunction.…”
Section: Posttreatment Managementmentioning
confidence: 99%